El camino del cisne negro: violencias en la construcción del sujeto en Black Swan - Gómez Cardeña, Sophia (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
The aim of this paper is to analyze the film Black Swan (2011), directed by Darren Aronofsky, in order to understand the identity construction of a subject crossed by multiple violence: Nina, the ballet dancer. For this purpose, the analysis will focus on the relationship of the following concepts: the processes of recognition, the dynamics of power and violence, and the experience of motherhood. It is concluded that Nina’s character suffers a double violence. The first one is linked to a patriarchal scheme of structural violence towards women and the feminine and the second one is related to an intimate and symbolic violence: the fusion and lack of recognition of her as a human being separated from her mother.

El objetivo de este ensayo es analizar la película Black Swan (2011), del director norteamericano Darren Aronofsky, para comprender la producción subjetiva de un sujeto atravesado por múltiples violencias: Nina, la bailarina de ballet protagonista del film. Para este propósito, se explicarán los procesos de reconocimiento, las dinámicas de poder y violencia, y la vivencia del cuerpo desarrollados a lo largo de la película. Se concluye que el personaje de Nina sufre una doble violencia, una ligada a un esquema patriarcal de violencia estructural contra las mujeres y lo femenino, y otra a nivel íntimo y vincular: la fusión y ausencia de reconocimiento de ella como un ser separado de su madre.
The Pathway of Black Swan: Violence and Construction of the Subject
Keywords: Hitos; Rurbanidad; Políticas públicas; Desarrollo social; Vida cotidiana; Organizaciones; https://purl.org/pe-repo/ocde/ford#5.09.01